Readiness Measurement of Integrated Stunting Prevention System Users (SIMPATI) Using Technology Readiness Index (TRI) - Siti Nida, Siti Nida Saripah (LPPM & Fakultas Teknologi Informasi UNSAP, 2024)
SIMPATI (Integrated Stunting Prevention System) is one of the Sumedang Digital Region programs in collaboration with the Sumedang Regency Government and Telkomsel to accelerate the handling of child development disorders or stunting. In 2018, the stunting rate in Sumedang Regency reached 32%. However, after implementing SIMPATI, the stunting prevalence rate in Sumedang district has decreased in the last five years, from 32.2% in 2018, to 8.27% in 2022. Seeing this success, the Minister of Health of the Republic of Indonesia (Menkes) Budi Gunadi Sadikin stated